Ecotoxicological and Genotoxic Evaluation of Buenos Aires City (Argentina) Hospital Wastewater - Anahí Magdaleno; Ángela Beatriz Juárez; Valeria Dragani; Magalí Elizabeth Saenz; Marta Paz; Juan Moretton (Journal of Toxicology)
Hospital wastewater (HWW) constitutes a potential risk to the ecosystems and human health due to the presence of toxic and genotoxic chemical compounds. In the present work we investigated toxicity and genotoxicity of wastewaters from the public hospital of Buenos Aires (Argentina). The effluent from the sewage treatment plant (STP) serving around 10 million inhabitants was also evaluated. The study was carried out between April and September 2012. Toxicity and genotoxicity assessment was performed using the green algae Pseudokirchneriella subcapitata and the Allium cepa test, respectively. Toxicity assay showed that 55% of the samples were toxic to the algae (%I of growth between 23.9 and 54.8). The A. cepa test showed that 40% of the samples were genotoxic. The analysis of chromosome aberrations (CA) and micronucleus (MN) showed no significant differences between days and significant differences between months. The sample from the STP was not genotoxic to A. cepa but toxic to the algae (%I = 41%), showing that sewage treatment was not totally effective. This study highlights the need for environmental control programs and the establishment of advanced and effective effluent treatment plants in the hospitals, which are merely dumping the wastewaters in the municipal sewerage system.